High-toughness aerogel as well as preparation method and application thereof
By constructing a rotane structure aerogel based on column [5] aromatic monomers, the aerogel shrinkage and brittleness problems are solved, and the combination of high mechanical properties and low density is achieved. It is suitable for lithium battery separators and other fields.
Patent Information
- Application Number
- CN202411270260.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
Existing aerogels are prone to shrink during the preparation process and are brittle due to their ultra-high porosity, making it difficult to achieve good mechanical properties and lightweight structure at the same time.
Using a rotane structure based on column [5] aromatic monomer, a mechanical interlocking structure is formed through the host-guest complexing, cross-linking and freeze-drying process of polyimine oligomer with column [5] aromatic monomer. High toughness aerogel.
It achieves the low density, high mechanical properties and good thermal insulation properties of aerogel, and is suitable for lithium battery separators and other fields, improving its mechanical properties and toughness while maintaining low density.
Smart Images

Figure CN119119565A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aerogels, and in particular relates to a high-toughness aerogel and a preparation method and application thereof. Background Art
[0002] Aerogel is an interconnected nanostructured porous material prepared by replacing liquid with gas. Its unique nanoporous structure gives aerogel unique properties such as low density, high surface area, high porosity and low thermal conductivity, making it have great potential in the fields of pollutant treatment, thermal insulation materials, sensors and heat storage devices. However, shrinkage problems are inevitable during the preparation of aerogels, and most aerogels are brittle due to their ultra-high porosity. Therefore, it has always been challenging to achieve good mechanical properties and lightweight structures at the same time. Ensuring low density while improving mechanical properties is an important research topic with academic and engineering value.
[0003] To date, many attempts have been reported to inhibit aerogel shrinkage and improve mechanical properties. For example, the gel is dried using a supercritical drying method to reduce or eliminate the effect of capillary forces on aerogel shrinkage. However, this method usually requires special equipment and operating techniques. In addition, blending and modifying aerogels with materials such as graphene, carbon nanotubes, and cellulose nanofibers to enhance the performance of aerogel materials is also a common strategy, but this method may lead to uneven aerogel structures. Recently, metal organic cages / polyhedrons (MOC / MOP) have also been used as porous structural units for making aerogels. By functionalizing the structure, aerogel materials with uniform structure and excellent mechanical properties are prepared at the molecular level, but the building blocks of this type of aerogel are limited. Therefore, it is of great significance to design new aerogel building blocks, study their structure-activity relationship from the perspective of molecular structure, and thus solve the problems of aerogel shrinkage and poor mechanical properties. Summary of the invention
[0004] Based on the above-mentioned shortcomings and deficiencies in the prior art, one of the objects of the present invention is to at least solve one or more of the above-mentioned problems in the prior art. In other words, one of the objects of the present invention is to provide a high-toughness aerogel and a preparation method and application thereof that meet one or more of the above-mentioned needs.
[0005] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0006] A high-toughness aerogel, the aerogel containing a rotaxane structure constructed based on pillar[5]arene monomers;
[0007] Among them, the structural formula of the pillar [5] aromatic monomer is:
[0008]
[0009] The present invention also provides a method for preparing the high-toughness aerogel as described in the above scheme, comprising the following steps:
[0010] (1) Preparation of column [5] aromatic monomers;
[0011] (2) host-guest complexation of polyimine oligomers with pillar[5]arene monomers dissolved in chloroform to prepare pillararene-based polyrotaxanes;
[0012] (3) After draining the polyrotaxane solvent, add chloroform until the polyrotaxane is fully dissolved to obtain a polyrotaxane solution;
[0013] (4) adding a solution of tris(2-aminoethylamine) dissolved in dimethyl sulfoxide into the polyrotaxane solution for end-capping and cross-linking to form a gel;
[0014] (5) The gel is aged, and then solvent exchange is performed after aging, and finally freeze-dried to obtain the aerogel.
[0015] As a preferred embodiment, the step (1) comprises the following steps:
[0016] (a) 1,6-dibromohexane and K2CO3 are added to a reaction vessel, and then hydroquinone dissolved in acetonitrile is added, and nitrogen is pumped and released several times, and the reaction is carried out at 80-90°C for at least 10 hours. After the reaction is completed, the liquid is filtered and rotary evaporated, mixed and passed through a column to obtain the product M1;
[0017] (b) dissolving the product M1 and p-phenylene dimethyl ether in 1,2-dichloroethane, adding paraformaldehyde, and then adding a catalyst boron trifluoride etherate to react while stirring. After the reaction is completed, quenching is performed with a saturated sodium bicarbonate solution, extracting, rotary evaporating, and mixing the material to pass through a column to obtain the product M2;
[0018] (c) dissolving the product M2 and potassium phthalimide in DMF, pumping and releasing nitrogen several times, and reacting at 80-95° C. for at least 10 hours. After the reaction, adding distilled water, rotary evaporation, and mixing the mixture to pass through a column to obtain the product M3;
[0019] (d) The product M3 is dissolved in methanol, and hydrazine hydrate is added, and the reaction is carried out at 80-90°C for at least 10 hours. After the reaction is completed, the product is cooled and filtered, and washed with methanol. The solid filtrate is taken and dried to obtain the column [5] aromatic monomer.
[0020] As a preferred embodiment, in step (a), the molar ratio of 1,6-dibromohexane: K2CO3: hydroquinone is (2-4): (2-3): 1;
[0021] Wherein, the molar concentration of hydroquinone is 0.3-0.4 mol / L.
[0022] As a preferred embodiment, in the step (b), the molar ratio of product M1: terephthalate: paraformaldehyde: boron trifluoride ether is 1: (7-9): (25-30): (8-10);
[0023] The molar concentration of the product M1 in 1,2-dichloroethane is 0.02-0.03 mol / L.
[0024] As a preferred embodiment, in the step (c), the molar ratio of the product M2: potassium phthalimide is 1:(2-4);
[0025] Among them, the molar concentration of product M2 in DMF is 0.015-0.025 mol / L.
[0026] As a preferred embodiment, the synthesis process of the polyimine oligomer comprises: a terephthalaldehyde solution dissolved in chloroform reacts with a 1,6-hexanediamine solution dissolved in methanol to form a polyimine oligomer; wherein the concentration of the terephthalaldehyde solution is 1.6-1.7 mol / L, the concentration of the 1,6-hexanediamine solution is 1.9-2.0 mol / L, the reaction time is 6-12 hours, and the reaction temperature is 20-35°C;
[0027] In the step (2), the concentration of the column [5] aromatic hydrocarbon monomer solution dissolved in chloroform is 0.04 to 0.06 mol / L, and the reaction time is 12 to 16 hours.
[0028] As a preferred embodiment, in step (4), the concentration of the tris(2-aminoethylamine) solution is 0.05-0.06 mol / L, and the reaction temperature is 20-35°C;
[0029] The volume ratio of terephthalaldehyde solution, 1,6-hexanediamine solution, column [5] aromatic hydrocarbon monomer solution and tris (2-aminoethylamine) solution is (1.95-2.05): 1: (0.95-1.05): (13.45-13.55).
[0030] As a preferred embodiment, in step (5), the aging temperature is 20 to 35° C. and the aging time is 24 to 36 hours;
[0031] The solvent exchange is divided into two steps:
[0032] In the first step, a mixture of dimethyl sulfoxide and anhydrous ethanol in different volume ratios is used to sequentially exchange solvents, wherein the volume ratio of dimethyl sulfoxide to anhydrous ethanol decreases sequentially, and the last one is all anhydrous ethanol;
[0033] In the second step, solvent exchange is performed in sequence using mixed solutions of anhydrous ethanol and water in different volume ratios, wherein the volume ratio of anhydrous ethanol to water decreases successively, and the last solution is all water.
[0034] The present invention also provides an aerogel as described in the above scheme or an aerogel prepared by the preparation method as described in any of the above schemes, which is used for a lithium battery separator.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The high-toughness aerogel of the present invention is a special structure realized by mechanical bonds. Unlike covalent and non-covalent compounds, it is an entanglement and interlocking of two or more components in space. The components cannot be separated without destroying or distorting the chemical bonds between atoms, and there is a high degree of conformational freedom. Intramolecular motion (i.e., elongation, rotation, sliding and twisting) can occur between interlocking components, providing a way to dissipate energy. The present invention introduces a mechanical interlocking structure based on polyrotaxane as a building block into aerogel. In this design, the macrocyclic main body can increase the distance between molecules to resist shrinkage, while the mechanical interlocking structure can be used as a cross-linking point to increase strength; the molecular motion of the interlocking structure consumes energy, thereby improving toughness. In view of the good mechanical properties, low thermal conductivity, hydrophobic properties of columnar aromatics, affinity of imine bonds in the cross-linking structure for lithium ions, and the porous structure of the aerogel itself that promotes lithium ion transport, the aerogel of the present invention can be applied to the fields of lithium battery separators. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The synthetic route of the P5-2NH2 monomer of Example 1 of the present invention;
[0038] Figure 2 The synthetic route of the P5 monomer of Comparative Example 2 of the present invention;
[0039] Figure 3 Schematic diagram of the building blocks and structure of aerogel;
[0040] Figure 4 As a model compound 1 H NMR spectrum;
[0041] Figure 5 For rotaxane 1 H NMR spectrum;
[0042] Figure 6 is the 2D NOESY NMR spectrum of rotaxane;
[0043] Figure 7 FTIR spectra of three types of aerogels;
[0044] Figure 8 The stress-strain and fracture energy curves of three types of aerogels;
[0045] Fig. 9 Thermal conductivity and density data of three types of aerogels;
[0046] Fig.10 This is the diagram of the aerogel water contact angle test and the water-oil separation device;
[0047] Fig.11 Aerogel lithium battery performance data;
[0048] Fig.12 Aerogel recyclability 1 H NMR spectrum. DETAILED DESCRIPTION
[0049] In order to more clearly illustrate the embodiments of the present invention, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those of ordinary skill in the art, other accompanying drawings and other implementation methods can be obtained based on these accompanying drawings without creative work.
[0050] The present invention aims at the shortcomings in the art and the defects such as brittleness due to ultra-high porosity in the process of obtaining aerogel. The present invention utilizes the property of mechanical interlocking structure to dissipate energy through intramolecular motion (i.e. elongation, rotation, sliding and twisting) to improve the mechanical properties of aerogel. In addition, the aerogel's own good mechanical properties, heat insulation, hydrophobicity and other properties are utilized to explore its application as lithium battery separator and other aspects.
[0051] The present invention introduces a rotaxane structure constructed based on pillar[5]arene into an aerogel, and prepares a low-density aerogel material with good mechanical properties through a simple aldehyde-amine condensation strategy and a freeze-drying process. For details, see the following Example 1.
[0052] Embodiment 1:
[0053] The method for preparing the aerogel of this embodiment includes the following steps:
[0054] (1) Preparation of column [5] aromatic monomers
[0055] The structural formula of the aromatic monomer of column [5] in this embodiment is:
[0056]
[0057] The specific preparation process is as follows Figure 1As shown, 1,6-dibromohexane and K2CO3 are first poured into a flask, and then hydroquinone dissolved in acetonitrile is slowly added, the molar concentration of hydroquinone is 0.36 mol / L, wherein the molar ratio of 1,6-dibromohexane: K2CO3: hydroquinone is 3:2.5:1, nitrogen is pumped and released three times, the reaction is carried out at 85°C overnight, the liquid is filtered out, the extracted solid is washed with dichloromethane, the liquid is filtered out again, rotary evaporation is performed, and the mixed material is passed through a column to obtain M1; M1 and p-phenylenedimethyl ether are dissolved in 1,2-dichloroethane, the molar concentration of M1 in 1,2-dichloroethane is 0.024 mol / L, and then paraformaldehyde is added, and the catalyst boron trifluoride etherate is slowly added while stirring, wherein the molar ratio of M1: p-phenylenedimethyl ether: paraformaldehyde: boron trifluoride etherate is 1:8:2 7:9, react for about 30 minutes (check with the plate at any time during the reaction), quench with saturated sodium bicarbonate solution after the reaction, extract, rotary evaporate, and pass the mixture through the column to obtain M2; M2 and potassium phthalimide are dissolved in DMF, the molar ratio of M2 to potassium phthalimide is 1:3, the molar concentration of M2 in DMF is 0.019 mol / L, nitrogen is pumped and released three times, react at 90°C overnight, add a large amount of distilled water and rotary evaporate at 80°C, the product is an oily substance, and pass the mixture through the column to obtain M3; M3 is dissolved in methanol, the molar concentration is 0.040 mol / L, and hydrazine hydrate is added, react at 75°C overnight, cool and filter, wash with methanol, take the filtrate solid, and dry it to obtain the product M4, i.e. column [5] aromatic monomer, referred to as P5-2NH2.
[0058] (2) Preparation of aerogel aero-3
[0059] At room temperature (25°C), 394.74 mg of terephthalaldehyde was dissolved in 1.8 mL of chloroform and reacted with 231 μL of 1,6-hexanediamine dissolved in 0.9 mL of methanol for 12 h to form a polyimine oligomer; 36 mg of P5-2NH2 dissolved in 0.9 mL of chloroform was added to react for 12 h to form a polyrotaxane structure; the polyrotaxane solvent was drained by a freeze dryer, and 1 mL of chloroform was added to dissolve the polyrotaxane; finally, 117 μL of tris(2-aminoethylamine) dissolved in 13.5 mL of dimethyl sulfoxide was added for end-capping and cross-linking to form a gel; after the gel was aged at room temperature for 36 h, eight solvent exchanges were carried out successively, and the solvents were dimethyl sulfoxide (DMSO) / anhydrous ethanol mixtures (4:1, 1:1, 1:4 and 0:4, v / v) and anhydrous ethanol / water mixtures (4:1, 1:1; 1:4 and 0:4, v / v), respectively; finally, aerogel aero-3 with good appearance was prepared by freeze drying.
[0060] Comparative Example 1:
[0061] The preparation method of the aerogel of this comparative example includes the following steps:
[0062] 394.74 mg of terephthalaldehyde was dissolved in 1.8 mL of chloroform and reacted with 231 μL of 1,6-hexanediamine dissolved in 0.9 mL of methanol for 12 h to form a polyimine oligomer; 0.9 mL of chloroform was added to react for another 12 h; the polyrotaxane solvent was drained by a freeze dryer, and 1 mL of chloroform was added to dissolve the polyrotaxane; finally, 117 μL of tris(2-aminoethylamine) dissolved in 13.5 mL of dimethyl sulfoxide was added for end-capping and cross-linking to form a gel; after the gel was aged at room temperature for 36 h, eight solvent exchanges were carried out successively, and the solvents were dimethyl sulfoxide (DMSO) / anhydrous ethanol mixture (4:1, 1:1, 1:4 and 0:4, v / v) and anhydrous ethanol / water mixture (4:1, 1:1; 1:4 and 0:4, v / v); finally, aerogel aero-1 with good appearance was prepared by freeze drying.
[0063] Comparative Example 2:
[0064] The preparation method of the aerogel of this comparative example includes the following steps:
[0065] (1) Preparation of P5 monomer
[0066] The structural formula of the P5 monomer in this comparative example is:
[0067]
[0068] The specific preparation process is as follows Figure 2 As shown, p-phenylenedimethyl ether is dissolved in 1,2-dichloroethane, the molar concentration of p-phenylenedimethyl ether in 1,2-dichloroethane is 0.192 mol / L, and then paraformaldehyde is added, and the catalyst boron trifluoride etherate is slowly added while stirring, wherein the molar ratio of p-phenylenedimethyl ether: paraformaldehyde: boron trifluoride etherate is 1:3:1, and the reaction is carried out for about 30 minutes (the plate is checked at any time during the reaction), and after the reaction is completed, it is quenched with saturated sodium bicarbonate solution, extracted, rotary evaporated, and mixed with the material to pass through a column to obtain P5.
[0069] (2) Preparation of aerogel aero-2
[0070] 394.74 mg of terephthalaldehyde was dissolved in 1.8 mL of chloroform and reacted with 231 μL of 1,6-hexanediamine dissolved in 0.9 mL of methanol for 12 h to form a polyimine oligomer; 36 mg of P5 dissolved in 0.9 mL of chloroform was added to react for 12 h to form a polyrotaxane structure; the polyrotaxane solvent was drained by a freeze dryer, and 1 mL of chloroform was added to dissolve the polyrotaxane; finally, 117 μL of tris(2-aminoethylamine) dissolved in 13.5 mL of dimethyl sulfoxide was added for end-capping and cross-linking to form a gel; after the gel was aged at room temperature for 36 h, eight solvent exchanges were carried out successively, and the solvents were dimethyl sulfoxide (DMSO) / anhydrous ethanol mixture (4:1, 1:1, 1:4 and 0:4, v / v) and anhydrous ethanol / water mixture (4:1, 1:1; 1:4 and 0:4, v / v), respectively; finally, aerogel aero-2 with good appearance was prepared by freeze drying.
[0071] In order to investigate whether pillararenes penetrate into the alkyl chains of the cross-linked network, a model compound M was designed. Figure 4 As shown, after the reaction of benzaldehyde and 1,6-hexanediamine, the aldehyde peak disappeared and the peak of the imine bond appeared, proving that M was successfully prepared. The synthetic route of M is as follows:
[0072]
[0073] After M and P5 are complexed, Figure 5 As shown in Figure 2, the aromatic protons in the polyimine alkyl chain shift upward, which is due to the shielding effect of the protons, consistent with the known host-guest complex properties. In order to study the relative spatial positions of the host and guest in the inclusion complex, 2D NOESY NMR experiments were performed, as shown in Figure 2. Figure 6 As shown, NOESY signals were found between the protons of the guest and the methylene groups of the host, indicating that these protons were in close proximity, confirming the successful preparation of polyimine oligomers and pillararenes to generate rotaxane structures.
[0074] like Figure 7 As shown, the three aerogels have –1 There is a C=N characteristic peak at 1690cm –1 The C=O stretching characteristic peak at 1503 cm-1 is very weak, proving the existence of imine bond formed by condensation of aldehyde and amine. -1 The strong benzene ring skeleton vibration is shown at the site, indicating that the columnar aromatics exist in the cross-linked network, which confirms the successful preparation of the three aerogels.
[0075] like Figure 8As shown in the figure, the elongation at break and the fracture energy of aero-3 and aero-2 are significantly higher than that of aero-1 aerogel, which is due to the fact that the mechanical interlocking structure can consume energy through slippage and rotation, disperse stress and avoid stress concentration. This confirms that the mechanical interlocking structure effectively improves the toughness of the aerogel.
[0076] like Fig. 9 and Fig.10 As shown, aerogels can be successfully used in fields such as thermal insulation and water-oil separation due to their own advantages such as low thermal conductivity and good hydrophobicity. In view of the characteristics of aerogels, their application in battery separators was further explored. First, the excellent mechanical properties of aerogels can prevent lithium dendrites from piercing. The hydrophobicity of aerogels can improve the wettability of the separator. Imine bonds are potential coordination sites, increasing the affinity for lithium ions. Low density also provides efficient transportation of lithium ions. Fig.11 (a, b) The results show that the mechanically interlocked aerogel aerogel-3 has a high ionic conductivity and voltage window, showing its good ion transport ability. Then the related charge and discharge performance and cycle stability performance test of aerogel-3 as a lithium battery film in lithium batteries were studied separately. Fig.11 From the CV curve shown in (c), it can be seen that after three cycles, the curves are very close in shape and position, indicating that aero-3 has stable electrochemical properties as a lithium battery film. Fig.11 (d, e) show the charge and discharge performance of lithium-ion batteries with aero-3 as lithium battery film at different rates. When the rate increases to 0.2C, 0.5C, 1C and 2C and then decreases to 0.1C, the capacity almost recovers to the initial value (about 160mAh / g). Fig.11 (f) shows that after 50 cycles at 0.5C, the capacity remains almost unchanged and the coulombic efficiency is close to 100%. All of the above indicate that aero-3 has excellent lithium battery performance and long cycle performance as a lithium-ion battery separator, and has broad application prospects in the field of lithium batteries. In addition, due to the presence of the imine bond, the aerogel is also recyclable. When aero-3 is placed in DMSO and a certain amount of trifluoroacetic acid is added, aero-3 is completely dissolved in the DMSO solution. Then, an equal molar amount of triethylamine is added to the trifluoroacetic acid, and the gel is regenerated, confirming the recyclability of the aerogel. Fig.12 As shown, after adding trifluoroacetic acid, the monomer peak reappeared in DMSO, indicating that aero-3 was degraded into monomers dissolved in DMSO solution. Then, after adding an equimolar amount of triethylamine, the monomer peak disappeared, indicating that the reaction between aero-3 monomers can regenerate gel. The recyclable performance of aero-3 is of great significance to environmental protection.
[0077] In view of the numerous embodiments of the scheme of the present invention, the raw materials and dosage involved can be selected according to actual needs within the limited range, and the experimental data of each embodiment is huge and numerous, which is not suitable for listing and explaining one by one here, but the content required to be verified and the final conclusion obtained in each embodiment are similar. Therefore, the verification content of each embodiment will not be explained one by one here.
[0078] The above description is only a detailed description of the preferred embodiments and principles of the present invention. For ordinary technicians in this field, according to the ideas provided by the present invention, there will be changes in the specific implementation methods, and these changes should also be regarded as the protection scope of the present invention.
Claims
1. A high-toughness aerogel, characterized in that: The aerogel contains a rotaxane structure constructed based on pillar[5]arene monomers; Among them, the structural formula of the pillar [5] aromatic monomer is:
2. The method for preparing a high-toughness aerogel according to claim 1, characterized in that: The following steps are involved: (1) Preparation of column [5] aromatic monomers; (2) host-guest complexation of polyimine oligomers with pillar[5]arene monomers dissolved in chloroform to prepare pillararene-based polyrotaxanes; (3) After draining the polyrotaxane solvent, add chloroform until the polyrotaxane is fully dissolved to obtain a polyrotaxane solution; (4) adding a solution of tris(2-aminoethylamine) dissolved in dimethyl sulfoxide into the polyrotaxane solution for end-capping and cross-linking to form a gel; (5) The gel is aged, and then solvent exchange is performed after aging, and finally freeze-dried to obtain the aerogel.
3. The preparation method according to claim 2, characterized in that: The step (1) comprises the following steps: (a) 1,6-dibromohexane and K2CO3 are added to a reaction vessel, and then hydroquinone dissolved in acetonitrile is added, and nitrogen is pumped and released several times, and the reaction is carried out at 80-90°C for at least 10 hours. After the reaction is completed, the liquid is filtered and rotary evaporated, mixed and passed through a column to obtain the product M1; (b) dissolving the product M1 and p-phenylene dimethyl ether in 1,2-dichloroethane, adding paraformaldehyde, and then adding a catalyst boron trifluoride etherate to react while stirring. After the reaction is completed, quenching is performed with a saturated sodium bicarbonate solution, extracting, rotary evaporating, and mixing the material to pass through a column to obtain the product M2; (c) dissolving the product M2 and potassium phthalimide in DMF, pumping and releasing nitrogen several times, and reacting at 80-95° C. for at least 10 hours. After the reaction, adding distilled water, rotary evaporation, and mixing the mixture to pass through a column to obtain the product M3; (d) The product M3 is dissolved in methanol, and hydrazine hydrate is added, and the reaction is carried out at 80-90°C for at least 10 hours. After the reaction is completed, the product is cooled and filtered, and washed with methanol. The solid filtrate is taken and dried to obtain the column [5] aromatic monomer.
4. The preparation method according to claim 3, characterized in that: In the step (a), the molar ratio of 1,6-dibromohexane: K2CO3: hydroquinone is (2-4): (2-3): 1; Wherein, the molar concentration of hydroquinone is 0.3-0.4 mol / L.
5. The preparation method according to claim 3, characterized in that: In the step (b), the molar ratio of product M1: terephthalate: paraformaldehyde: boron trifluoride ether is 1: (7-9): (25-30): (8-10); The molar concentration of the product M1 in 1,2-dichloroethane is 0.02-0.03 mol / L.
6. The preparation method according to claim 3, characterized in that: In the step (c), the molar ratio of product M2: potassium phthalimide is 1:(2-4); Among them, the molar concentration of product M2 in DMF is 0.015-0.025 mol / L.
7. The preparation method according to claim 2, characterized in that: The synthesis process of the polyimine oligomer comprises: a terephthalaldehyde solution dissolved in chloroform reacts with a 1,6-hexanediamine solution dissolved in methanol to form a polyimine oligomer; wherein the concentration of the terephthalaldehyde solution is 1.6-1.7 mol / L, the concentration of the 1,6-hexanediamine solution is 1.9-2.0 mol / L, the reaction time is 6-12 hours, and the reaction temperature is 20-35° C.; In the step (2), the concentration of the column [5] aromatic hydrocarbon monomer solution dissolved in chloroform is 0.04 to 0.06 mol / L, and the reaction time is 12 to 16 hours.
8. The preparation method according to claim 7, characterized in that: In the step (4), the concentration of the tris(2-aminoethylamine) solution is 0.05-0.06 mol / L, and the reaction temperature is 20-35° C.; The volume ratio of terephthalaldehyde solution, 1,6-hexanediamine solution, column [5] aromatic hydrocarbon monomer solution and tris (2-aminoethylamine) solution is (1.95-2.05): 1: (0.95-1.05): (13.45-13.55).
9. The preparation method according to claim 2, characterized in that: In the step (5), the aging temperature is 20 to 35° C. and the aging time is 24 to 36 hours; The solvent exchange is divided into two steps: In the first step, a mixture of dimethyl sulfoxide and anhydrous ethanol in different volume ratios is used to sequentially exchange solvents, wherein the volume ratio of dimethyl sulfoxide to anhydrous ethanol decreases sequentially, and the last one is all anhydrous ethanol; In the second step, solvent exchange is performed in sequence using mixed solutions of anhydrous ethanol and water in different volume ratios, wherein the volume ratio of anhydrous ethanol to water decreases successively, and the last solution is all water.
10. The high-toughness aerogel according to claim 1 or the high-toughness aerogel prepared by the preparation method according to any one of claims 2 to 9, characterized in that: Used in lithium battery separators.
